Teddy Fay: Smooth Operator - Book 1 - Woods, Stuart; Hall, Parnell; Roberts, Tony, 1939-; Penguin Audio (Firm) (New York : Penguin Random House, 2016)
When President Kate Lee calls Stone Barrington to Washington on an urgent matter, it's soon clear that a potentially disastrous situation requires the kind of help more delicate than even he can provide--and he knows just the right man for the job: Teddy Fay, ex-CIA, master of disguise, and a gentleman not known for abiding by legal niceties in the pursuit of his own brand of justice.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Intelligence officers -- Fiction -- United States; Private investigators -- Fiction; Audiobooks; Washington (D.C.) -- Fiction; Detective and mystery fiction; Action and adventure fiction; Audiobooks